Desempenho da produtividade total dos fatores (PTF), na agropecuária das mesorregiões de Goiás entre 1970 e 2017 - Mello Júnior, Fernando Corrêa de (2023)
During the 1970s, the process known as agricultural modernization began in the state of Goiás, a little later than in the rest of Brazil, which started in the 1950s. Enabled mainly by public policies promoting regional development and abundant financing, the cerrado region of Goiás saw the introduction of new techniques capable of boosting productivity in the sector, as well as machinery, equipment, and inputs. This work contributes in two aspects i) to the literature, by providing a study of a geographical and regional scope that has not yet been explored; ii) it fills a gap in the detailed analysis of the state of Goiás, which is the fifth largest agricultural producer in the country in terms of Gross Value of Agricultural Production (VBP) in 2022. For the parties involved, it provides analytical evidence of the homogeneity or heterogeneity of the state's productivity, shedding light on state public policies and market decisions made by the productive agents. Given this scenario and the importance of agriculture for Goiás, the objective of this work is to analyze and compare the performance of agricultural Total Factor Productivity (TFP) in Goiás and its different Mesoregions. TFP was chosen as a proxy for productivity. The methodology used focused on analyzing TFP between 1970 and 2017, and its inputs and output indices calculated using the Törnqvist index (1936). The results showed that, starting from 1970, agricultural productivity in the Southern Mesoregion grew at a higher rate than that observed in the state of Goiás and the adjacent mesoregions, with the Capital index experiencing higher growth compared to Labor and Land indices from the same decade, indicating a shift towards largescale production in the regional agriculture, increasing labor and land productivity. The Eastern Mesoregion had the second highest annual growth rate of TFP during the study period, with a 0.13 percentage point difference from the leader. The performance of the Eastern Mesoregion was linked to the increase in the output index in the last two censuses, facilitated by irrigated crops using central pivots. The North and Northwest regions followed trajectories where livestock products had smaller increases in the output index compared to agricultural products, from 1970 to 2017, representing the main contributions to the agricultural value. On the other hand, the Central Mesoregion diverged from the state average of agricultural TFP, as land use for agricultural activities and labor experienced declines starting from 1985, resulting in the lowest average TFP growth during the analyzed period.